THE INFECTION OF COCCIDIA AND STRONGYLOIDES IN BALI CATTLE POST-MINERAL ADMINISTRATION - Putra, Komang Yogie Suryana; Apsari, Ida Ayu Pasti; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2017)
The research has been conducted to find out the infection of coccidia and strongyloides in bali cattle, after the administration of minerals in varying amount. The examined samples were 24 feces of bali cattle, which were divided into four treatment groups: without mineral administration (control group), mineral administration of 2.5 gram/head/day; 5.0 gram/ head/day; and 7.5 grams/head/day. After three months administration, examination of coccidia and strongyloides infection was performed using sedimentation concentration and floatation method with saturated salt substance. The data obtained were nominal data which analyzed by using chi square test.  The results showed that faecal examination in the bali cattle that were not given mineral treatment (control) was found ookista coccidia and larvae strongyloides. However, no coccidia and strongyloides infection in bali cattle found in the minerals administration (2.5, 5.0, 7.5 gr/d) groups.